Valuing Technology Complementarities: Rooftop Solar and Energy Storage - Bryan Bollinger; Naim R. Darghouth; Kenneth T. Gillingham; Andres Gonzalez-Lira (Center for Economic Studies and ifo Institute (CESifo), 2023)
Product complementarities can shape market patterns, influencing the demand for related products and their accessories. This study examines complementarities in the demand for rooftop solar and an accessory, battery energy storage. Using nationwide administrative data, we estimate a dynamic nested-logit model of solar and storage adoption. We quantify the demand complementarity between solar and storage, and find that if storage was not available, 20% of households who coadopt solar and storage would not adopt anything. We find that the demand for solar and storage bundles increases with power outages, with a larger effect in California.
Keywords: C51; L94; Q48; Q58; 330; product complementarity; electricity resilience; demand estimation; new technology